2022
DOI: 10.1128/jvi.02146-21
|View full text |Cite
|
Sign up to set email alerts
|

The Orthobunyavirus Germiston Enters Host Cells from Late Endosomes

Abstract: With more than 80 members worldwide, the Orthobunyavirus genus in the Peribunyaviridae family is a large genus of enveloped RNA viruses, many of which are emerging pathogens in humans and livestock. How orthobunyaviruses (OBVs) penetrate and infect mammalian host cells remains poorly characterized. Here, we investigated the entry mechanisms of the OBV Germiston (GERV). Viral particles were visualized by cryo-electron microscopy and appeared roughly spherical with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Our results indicate that GlcCer was also embedded in both TOSV and GERV particles. GERV belongs to the Peribunyaviridae family, which is closely related to the Phenuiviridae family (Windhaber et al, 2022), and similar like phenuiviruses, peribunyaviruses bud into Golgi compartments (Elliott, 2014; Elliott and Brennan, 2014; Léger and Lozach, 2015). In contrast, SFV and EBOVLPs assemble at the plasma membrane, and our analysis showed no significant level of GlcCer level in their respective viral envelope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results indicate that GlcCer was also embedded in both TOSV and GERV particles. GERV belongs to the Peribunyaviridae family, which is closely related to the Phenuiviridae family (Windhaber et al, 2022), and similar like phenuiviruses, peribunyaviruses bud into Golgi compartments (Elliott, 2014; Elliott and Brennan, 2014; Léger and Lozach, 2015). In contrast, SFV and EBOVLPs assemble at the plasma membrane, and our analysis showed no significant level of GlcCer level in their respective viral envelope.…”
Section: Discussionmentioning
confidence: 99%
“…UUKV strain 23 was obtained from plasmids and amplified in BHK-21 cells (Mazelier et al 2016). The prototype strains of SFV, TOSV ISS, and GERV have been described previously (Pettersson and Kääriäinen, 1973; Helenius et al, 1980; Giorgi et al, 1991; Overby et al, 2006; Windhaber et al, 2022). All viruses were produced in BHK-21 cells and purified and titrated according to standard procedures (Meier et al, 2014; Léger et al, 2016; Hoffmann et al, 2018; Windhaber et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bafilomycin A1 (BioViotica), colcemid (Cayman Chemical), concanamycin B (BioViotica), MG-132 (Selleck Chemicals), nocodazole (Merck) and taxol (Merck) were all dissolved in 100% dimethyl sulfoxide (DMSO) to prepare stock solutions at 100 µM, 10 mM, 50 µM, 40 mM, 20 mM and 10 mM, respectively. Stock solutions of all drugs were diluted in DMEM at the indicated doses (Figures 1 and 4), which are known not to cause cytotoxicity ( 23, 34 ). Both dH 2 O and DMSO were included as solvent controls.…”
Section: Methodsmentioning
confidence: 99%
“…However, the low resolution of our subtomogram average (STA) and the lack of atomic models for HAZV GPs prevented a detailed structural understanding of the effect of K + on the GPs. Of note, it has recently been shown that disruption of the cellular K + gradient using KCl or the K + ionophore valinomycin inhibits infection by the peribunyaviruses La Crosse virus (LACV), keystone virus and Germiston virus; and of the phenuivirus RVFV (14,15), suggesting that K + is broadly required during bunyavirus entry.…”
Section: Introductionmentioning
confidence: 99%